The Use of an rGO Semi-transparent Organic Electrode in a ZnO Schottky Diode for UV Detection - Vieira, Douglas Henrique [UNESP]; Lima, Alessandro Henrique; da Silva Ozório, Maíza [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Quirino, Welber Gianini; Alves, Neri [UNESP] (Springer Nature, 2019)
Successful manufacture of a simple, low cost sprayed Schottky diode compatible with printed electronics using reduced graphene oxide (rGO) as a semi-transparent top electrode and zinc oxide (ZnO) as active layer has been reported in this paper. The rGO was synthesized using modified Hummers’ method and deposited by spray coating. The transmittance analyses of rGO films shows 62.3% transparency for ultraviolet (UV) light and by the Van der Pauw method shows sheet resistance of 19 kΩ/□. The rGO electrode provides an alternative to expensive metallic electrodes such as Au, Pt, Pd and Ag which are not ecofriendly. Furthermore, rGO performs Schottky contact with sprayed zinc oxide film resulting in a diode with the sequence of deposited layers Al/ZnO/rGO and low turn-on voltage that has current–voltage characteristics whose rectifying behavior is affected by the incidence of UV light resulting in a possibility to use that diode as photodetector for this kind of radiation.
Keywords: organic electrode; Reduced graphene oxide; Schottky diode; sprayer deposition; UV detection; zinc oxide